Rancang Bangun Media Pengenalan Rambu-rambu Lalulintas Dengan Memanfaatkan Teknologi Augmented Reality - Kurniawan Teguh Martono (AITI, 2016)
Traffic safety became one of the priorities that should be prioritized and considered. Safety riding is the behavior of motorists who are more concerned both for the safety, comfort and compliance with traffic regulations in order to prevent the risk of traffic accidents, as is done for the safety for the driver and passengers. Prevention efforts to minimize the human factor in traffic offenses, can be done by providing information knowledge learning about the discipline of traffic to the children since early ages, especially children 7 years of age because at the age of the children are able to read and count, both on the education level elementarythrough to high school / vocational school up to college students. This research, the process of designing multimedia applications that can be used in early education about the function and role of traffic signs by using Augmented Reality technology. With the design of multimedia applications is expected to add media education for the people in the know and learn about traffic signs, so that the number of traffic violations can be reduced.The results obtained from this research is the process of designsuccessfully performed with marked that the application can be run in accordance with the scenario. In addition the results of the test using black box showed that the results obtained in accordance with the expected results. Additionally marker failed to be detected if the distance the camera with a marker less than 10 ± 0.05 cm or more than 75 ± 0.05 cm and the angle between the marker below 40 ± 0,5O or more than 140 ± 0,5O.